A Randomised Controlled Trial of Clinician-Guided Internet-Based Cognitive Behavioural Therapy for Depressed Patients in Singapore - Lu, Sharon H. X.; Assudani, Hanita A.; Kwek, Tammie R. R.; Ng, Shaun W. H.; Teoh, Trisha E. L.; Tan, Geoffrey C. Y. (Frontiers in Psychology, 2021)
This study examined the efficacy and acceptability of a hybrid, clinician-guided internet-based Cognitive Behavioural Therapy (iCBT) programme for outpatients with depression in a psychiatric hospital in Singapore. Fifty three participants were randomly assigned to a treatment or wait-list control group before they underwent a cross-over of conditions. Treatment consisted of a 4-week iCBT with three face-to-face sessions. 60.9% of participants who received treatment completed all six modules. Intention-to-treat analysis showed treatment was associated with significant reductions in symptoms of depression, anxiety and psychological distress but not in functional impairment, while the control condition was not associated with changes in any measures. These reductions had moderate to large effect sizes (ESs) for symptoms of depression and anxiety, and moderate ES for psychological distress. The between-group difference in depression score had a moderate ES. There was a significant between-group treatment effect in depressive symptoms, but not in the other measures. Treatment gains were maintained at 3-month follow-up. Most of the participants were highly satisfied with the programme, with 90 percent stating they would recommend it. This is the first RCT to provide preliminary evidence for the efficacy and acceptability of iCBT for depression in Singapore.